DEMOGRAPHY OF ALPINE SHORT-LIVED PLANTS, LONGEVITY AND ONTOGENY STAGE DURATIONS - E. S. Kazantseva; V. G. Medvedev; V. G. Onipchenko (Юг России: экология, развитие)
The aim - to evaluate lifespan (full cycle) and ontogeny stage durations of nine alpine short-lived North- West Caucasus plants.Methods. For calculation we used a new method which was developed and suggested earlier by us. This method is based on a discrete ontogeny description and on the probability theory and random processes. The data on the monitoring of the marked individuals were collected during six years.Results. We found out that the lifespan of Anthyllis vulneraria is 2.6±0.3 years (hereinafter “±” is Standard error), Draba hispida – 4.5±0.3, Murbeckiella huetii – 4.6±1.1, Carum meifolium – 7.8±1.4, Eritrichium caucasicum – 9.1±1.4, Trifolium badium – 10.3±2.6, Sedum tenellum – 11±2.05, Androsace albana – 12.1±2.5, Minuartia recurva – 22.9±4.5. Also we demonstrated the matrix population models for studied plants, which show the probability of transition of individuals from one ontogeny stage to another in time interval (in our experiment – 1 year).Conclusion. Mortality of seedlings and juvenile plants, except Murbeckiella huetii, is around and more than 50%. Two years is the minimal amount of time that is necessary for full cycle of short-lived alpine plants, as it was shown for Anthyllis vulneraria, Murbeckiella huetii и Trifolium badium. A 3-12 years lifespan was calculated for other studied species. Persistence of Eritrichium caucasicum and Androsace albana populations provided by resistance of adult vegetative plants.